Glitter is not forever! Resource sharing and Knowledge sharing as the new sparkle in realizing development goals in Botswana through library resource sharing - Kelebogile Ramotsisi, Gobonetse (ADA University Library, 2024)
Botswana like the rest of the world is moving from resource based to knowledge-driven economy. Botswana’s economy has for the longest time been heavily dependent on Diamonds as a source of wealth. The country has since realized that that Diamonds are not forever, hence the need to diversify and join the world in creating wealth through knowledge creation and knowledge monetization. This realization has made Botswana to make major changes to its education system to begin to produce a new workforce which will create new knowledge and a new economy in the knowledge –driven dispensation. The government has started installing internet in schools and in small villages. Unfortunately Library budgets have been dwindling, thus restricting Libraries ability to subscribe to scholarly databases like, Emerald, Taylor and Francis, Elsevier and Science Direct among many others which are crucial in any Research institute. The article will examine the extent to which Botswana library consortia has enabled small library that cannot afford expensive databases to serve their clients through resource sharing. The paper will further discuss the impact of EIFL (Electronic Information for Libraries) initiatives in assisting small libraries in Botswana to overcome the burden of paywalls. The article will explore how resource sharing is bridging the gap that has been caused by many factors including the just ended pandemic. It will explore how the consortium has brought in a new hope for libraries to contribute to the achievement of sustainable development goals and assurance of a knowledge based society.
Keywords: Resource sharing; Inter-lending; Library consortia; inclusiveness